What is the value of hazardous weather forecasts? Evidence from a survey of backcountry skiers - Anna Alberini; Christoph M. Rheinberger; Andrea Leiter; Charles A. McCormick; Andrew Mizrahi (Fondazione Eni Enrico Mattei (FEEM), 2010)
What is the value of hazardous weather warnings? To answer this question, we focus on the avalanche bulletin for Switzerland issued by the WSL Institute for Snow and Avalanche Research (SLF). We take a survey-based, non-market valuation approach to estimating the value of hypothetical improvements in avalanche forecasting. We focus on backcountry skiers because (i) safety is arguably the most important type of benefit associated with the avalanche bulletin, (ii) they voluntarily undertake risks, and (iii) they perceive themselves and are generally perceived by others as skilled in avoiding risks. The respondents' willingness to pay (WTP) for the improved services ranges between CHF 42 to 46, implying a mean value of statistical life (VSL) of CHF 1.75 million. We find that WTP increases with income and is higher among Swiss nationals and those who rate the current bulletin 'useful.' Risk-tolerant individuals, persons who assessed their personal risk as lower than average, professional guides, and those who perceive themselves as proficient in using the existing bulletin report lower WTP figures. This suggests that the monetized value that people place on the enhanced bulletin reflects how productive these individuals are (or think they are) in using information to avoid avalanche risks.
Keywords: D81; J17; Q26; 330; Avalanche Risk; Mortality; Value of Hazardous Weather Forecasts; Contingent Valuation; Value of a Statistical Life